Combustion behavior of single particles from three different coal ranks and from sugar cane bagasse in O 2/N 2 and O 2/CO 2 atmospheres - Khatami, Reza; Stivers, Chris; Joshi, Kulbhushan; Levendis, Yiannis A.; Sarofim, Adel F. (Combustion and flame, 2012)
The combustion behavior of single fuel particles was assessed in O 2/N 2 and O 2/CO 2 background gases, with oxygen mole fractions in the range of 20–100%. Fuels included four pulverized coals from different ranks (a high-volatile bituminous, a sub-bituminous and two lignites) as well as pulverized sugarcane-bagasse, a biomass residue. Particles of 75–90 μm were injected under laminar flow in a bench-scale, transparent drop-tube furnace (DTF), electrically-heated to 1400 K where, upon experiencing high heating rates, they ignited and burned. The combustion of individual particles was observed with three-color optical pyrometry and high-speed high-resolution cinematography to obtain temperature and burnout time histories. Based on combined observations from these techniques, a comprehensive understanding of the behaviors of these fuels was developed under a variety of conditions, including simulated oxy-fuel combustion. The fuels exhibited distinct combustion behaviors. In air, the bituminous coal particles burned in two distinctive modes; the volatiles burned in bright envelope flames surrounding the devolatilizing char particles followed by heterogeneous char combustion. The volatile matter of sub-bituminous coal particles burned either in subdued envelope flames, surrounding devolatilizing and occasionally fragmenting chars, or heterogeneously at the char surface. Lignite particles typically burned with extensive fragmentation, and their volatiles burned simultaneously with the char fragments. The volatiles of bagasse particles burned in spherical and transparent envelope flames. Increasing the oxygen mole fraction in N 2, increased flame and char surface temperatures, and decreased burnout times; particles of all fuels burned more intensely with an increasing tendency of the volatiles to burn closer to the char surface. When the background gas N 2 was substituted with CO 2, the combustion of all fuels was distinctly less intense; at moderate O 2 mole fractions (<30%) most particles did not ignite under active flow conditions in the furnace (they did ignite under quiescent gas flow conditions in the DTF). Increasing the oxygen mole fraction in CO 2 increased the likelihood of combustion and its intensity. Combustion of volatiles in envelope flames was suppressed in the presence of CO 2, particularly under active gas flow in the DTF.